Connectivity of Communication Networks - Mao, Guoqiang; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book introduces a number of recent developments on connectivity of communication networks, ranging from connectivity of large static networks and connectivity of highly dynamic networks to connectivity of small to medium sized networks. This book also introduces some applications of connectivity studies in network optimization, in network localization, and in estimating distances between nodes. The book starts with an overview of the fundamental concepts, models, tools, and methodologies used for connectivity studies. The rest of the chapters are divided into four parts: connectivity of large static networks, connectivity of highly dynamic networks, connectivity of small to medium sized networks, and applications of connectivity studies.
1. Introduction -- Part 1. Connectivity of Large Static Networks -- 2. Large Network Models and Their Implications -- 3. Connectivity of Large Wireless Networks: Sufficient and Necessary Conditions -- 4. Giant Component in Large Wireless Networks -- 5. Critical Density for Percolation -- 6. Phase Transitions in Large Networks -- 7. Connectivity of Large Wireless Networks in the Presence of Interference -- Part 2. Connectivity of Highly Dynamic Networks -- 8. Connectivity of Dynamic Networks -- 9. Information Propagation in One-Dimensional Dynamic Networks -- 10. Information Propagation in Two-Dimensional Dynamic Networks -- Part 3. Connectivity of Small to Medium Sized Networks -- 11. Connectivity of One-Dimensional Small to Medium Sized Networks -- 12. Connectivity of Two-Dimensional Small to Medium Sized Networks -- 13. A New Measure of Wireless Network Connectivity -- Part 4. Applications of Connectivity Studies -- 14. Applications of Connectivity Studies.
Keywords: Telecommunication; Security systems; Computer networks .; Communications Engineering, Networks; Security Science and Technology; Computer Communication Networks